Legal Consequences for Foreign Medical Personnel Providing Health Services in Indonesia without A Practice License - Haekal Fahmi; Anak Agung Gede Duwira Hadi Santosa; I Gde Sastra Winata (GLOBAL HEALTH SCIENCE GROUP, 2026)
The utilization of foreign health workers in Indonesia has become an increasingly common phenomenon in line with the development of globalization and cross-border mobility. The purpose of this study is to identify and analyze the legal consequences of foreign medical personnel providing health services in Indonesia without a practice license. This study uses a normative research design, and the method of collecting legal sources in this study is document study. Documentary study can be described as a method of collecting several documents related to the issue being studied, both from primary and secondary legal materials. Collection of Normative Legal Materials The main methods used to collect normative legal materials are Library Research and Documentary Research. The legal materials sought are classified into three types: Primary Legal Materials (in the form of legislation), secondary legal materials (law books/literature, legal research journals), and tertiary legal materials (law dictionaries, law encyclopedias). After all the data has been collected, it is then reviewed and interpreted in relation to legal principles and theories The results of this study are that foreign medical personnel must fulfill several requirements before practicing in Indonesia, such as licensing, certification and registration, competency tests, areas of foreign medical personnel and accompanying personnel, time restrictions, and compensation. Based on the Health Law as stipulated in Article 442, sanctions are imposed on any foreign medical personnel who intentionally practice in Indonesia without a SIP, which can result in the medical or health personnel being punished with a maximum imprisonment of 5 (five) years or a maximum fine of Rp. 500,000,000.00 Efforts to take action against foreign medical personnel by the Ministry of Health and Professional Organizations include guidance and mediation by professional organizations, internal guidance by health agencies, verbal and written warnings by health agencies, guidance, supervision, and control by health agency personnel, revocation of licenses, and revocation of practice.